1999
DOI: 10.1002/(sici)1521-4028(199906)39:3<213::aid-jobm213>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Agaridiol, a new 1-arylpropane-1,2-diol produced byAgaricus sp.

Abstract: The new metabolite agaridiol (1) was isolated from cultures of Agaricus sp., and its structure was elucidated by mass spectrometric and NMR spectroscopic investigations. It shows moderate anti‐microbial activity against Bacillus subtilis ATCC 6633.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Few investigations into the antimicrobial activity of medicinal mushrooms have been carried out, and even fewer regarding oral microorganisms (Osaki et al, 1994;Berg et al, 1999;Paccola et al, 2001;Rosa et al, 2003;Grinde et al, 2006;Faccin et al, 2007). Hence, the aim of this article is to report the antimicrobial activity of three ethanol extracts of A. brasiliensis against mutans streptococci.…”
Section: Introductionmentioning
confidence: 99%
“…Few investigations into the antimicrobial activity of medicinal mushrooms have been carried out, and even fewer regarding oral microorganisms (Osaki et al, 1994;Berg et al, 1999;Paccola et al, 2001;Rosa et al, 2003;Grinde et al, 2006;Faccin et al, 2007). Hence, the aim of this article is to report the antimicrobial activity of three ethanol extracts of A. brasiliensis against mutans streptococci.…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, Berg et al isolated a new diol, agaridiol, from Agaricus sp. mycelium, which showed moderate antimicrobial activity against Bacillus subtilis ATCC6633, with 200 mg of the compound per 9 mm agar pore producing a zone of inhibition with a diameter of 16 mm [20].In 2011, Munkhgerel et al urea was isolated from A. silvaticus Schaeff ex. Secr substrate [2].In 2011, Ueguchi et al found N-benzoyl-L-leucine methyl ester from A. blazei substrate, which is the first time that this compound was isolated from nature [4].…”
Section: Other Nitrogenous Compoundsmentioning
confidence: 99%